The Comparative Analysis between Real Variable and Monetary Approach in Estimating and Forecasting Foreign Exchange Rate of Rupiah - SUPRAYITNO, Bambang (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
This paper aims to compare forecasting foreign exchange rate between real variable approach and monetary approach. Estimation model of ECM is used to estimate and forecast through those approaches. Completing the comparison, We also involve estimating and forecasting through adaptive expectation, we run ARIMA model to estimate and forecast real exchange rate. We utilize data of Indonesia in 1979 – 2000 to estimate the models. Parameter resulted is used to forecast ( ex post ) real exchange rate in interval 2001-2009. Empirical analysis shows that ARIMA’s prediction trend follows nearest the actual. The analysis supports the fact which is provide by step by step forecasting and explain that ARIMA outperform than others in 1 st three years (2001-2003), the 2 nd (2004-2006), the 3 rd (2007-2009), and all of nine years horizon forecasting. It also shows that MON consistently outperforms REAL. One of interesting points, REAL outperforms all method in the longer observation (all observation in estimating parameters).